2011
DOI: 10.1074/jbc.m110.169391
|View full text |Cite
|
Sign up to set email alerts
|

A WNT/β-Catenin Signaling Activator, R-spondin, Plays Positive Regulatory Roles during Skeletal Myogenesis

Abstract: R-spondins (RSPOs) are a recently characterized family of secreted proteins that activate WNT/␤-catenin signaling. In this study, we investigated the potential roles of the RSPO proteins during myogenic differentiation. Overexpression of the Rspo1 gene or administration of recombinant RSPO2 protein enhanced mRNA and protein expression of a basic helix-loophelix (bHLH) class myogenic determination factor, MYF5, in both C2C12 myoblasts and primary satellite cells, whereas MYOD or PAX7 expression was not affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 49 publications
2
84
0
2
Order By: Relevance
“…This condition is called hypertrophy and multiple studies identified different roles for canonical and non-canonical Wnt signaling in muscle fiber hypertrophy (Armstrong and Esser, 2005;Bernardi et al, 2011;Han et al, 2011;Rochat et al, 2004;von Maltzahn et al, 2011). Furthermore, expression of β-catenin is a prerequisite for the physiological growth of adult skeletal muscle, underscoring the importance of canonical Wnt signaling (Armstrong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This condition is called hypertrophy and multiple studies identified different roles for canonical and non-canonical Wnt signaling in muscle fiber hypertrophy (Armstrong and Esser, 2005;Bernardi et al, 2011;Han et al, 2011;Rochat et al, 2004;von Maltzahn et al, 2011). Furthermore, expression of β-catenin is a prerequisite for the physiological growth of adult skeletal muscle, underscoring the importance of canonical Wnt signaling (Armstrong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, inhibition of GSK3␤ results in activated WNT/␤-catenin signaling and leads to enhanced differentiation of C2 myogenic cells (60). The RSPO family of proteins, WNT/␤-catenin signaling agonists, can promote myogenic differentiation in cell culture (55). Pharmacological activations of WNT/␤-catenin signaling can also facilitate the differentiation of satellite cells and myoblasts (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the R-spondin family (RSPO) of secreted cysteine-rich proteins (RSPO1, -2, -3, and -4) activate the WNT/␤-catenin signaling pathway at the receptor level (53,54). RSPO2 promotes myogenic differentiation and myocyte fusion via activation of WNT/␤-catenin signaling in C2C12 cells (55). RSPOs can regulate WNT receptor expression and control myogenesis through gene expression of the transforming growth factor ␤ (TGF␤) antagonist Fst (56).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Armstrong et al have reported that the expression of -catenin is necessary for physiological growth of skeletal muscle and that Wnt signaling pathway induces -catenin activation of growth-control genes during overload induced skeletal muscle hypertrophy [209,210]. By using C2C12 and satellite cells, Han et al reported recently that activation of canonical pathway by R-spondin2, promote myogenic differentiation and hypertrophic myofiber formation [211]. When LiCl was added to the culture medium, the area of myotubes and index fusion were increased in both C2C12 and satellite cells, reaching values similar to those observed after Wnt4-induced hypertrophy [37].…”
Section: Wnt-related Regulation Of Myoblast Proliferation and Differementioning
confidence: 99%